Leadership Values and Government Ethics in The Character of Tobirama Senju: Reflections for Leaders of Today - Maulana, Achmad Amzal; Ampauleng, Ampauleng; Abdullah, Salma; Fatimah, Siti (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study examines the leadership values and governance ethics reflected in the character of Tobirama Senju, a fictional character from the Naruto series, as a reflection and inspiration for today's leaders. Tobirama Senju is known as a firm, innovative leader, and has a high commitment to justice and stability of government. Through a qualitative-descriptive approach, this study analyzes the various actions, decisions, and policies taken by Tobirama in the context of a fictional world, then relates them to the theories of leadership and ethics of modern government. The results of the analysis show that Tobirama not only prioritizes the aspect of power, but also balances it with the principles of morality, transparency, and social responsibility. Values such as integrity, justice, policy innovation, and concern for the welfare of the community are the main foundations of his leadership. The study also highlights the relevance of Tobirama's character as an adaptive and ethical leadership model in the midst of the challenges of the times, and provides recommendations for today's leaders to internalize these values in government practice. Thus, this research contributes to enriching the discourse of government science through an interdisciplinary approach that combines fictional character analysis with real needs in contemporary governance.